The gendered trickle-down effect: How mid-level managers' satisfaction with senior managers' supervision affects line employee's turnover intentions. Issue 7 (4th November 2014) - Chen, Ying; Friedman, Ray; Simons, Tony
Abstract : Purpose: – Voluntary employee turnover can be a challenge for all industries but high employee turnover has been a special concern in the hospitality industry, which is the context of this paper. The purpose of this paper is to incorporate a "trickle-down" perspective into the conventional research on turnover intention and satisfaction with supervision. The authors assess whether mid-level managers' satisfaction with senior managers' supervision is related positively to line employees' satisfaction with mid-level managers' supervision and, in turn, line employees' turnover intentions. Further, the authors examine whether the strength of this "trickle-down" effect is affected by the middle managers' gender. Design/methodology/approach: – The authors tested our theoretical argument using a sample of 1, 527 full-time employees in 267 different departments at 94 hotels in the USA and Canada. Hierarchical linear modeling was employed to analyze the data. Findings: – The authors found a trickle-down effect of satisfaction with supervision, as predicted, and the effect was stronger for female than male middle managers. These findings open new avenues for addressing turnover issues for organizations and managers. Originality/value: – This study extends the line of research on leadership and turnover in three ways. First, it shows how senior managers, who have no direct contact with line employees, can affect turnover intentions of line employees. Second, this research helps the authors know where to target efforts at intervention; by connecting middle managers' satisfaction with supervision with employees' turnover intentions, the authors know to target interventions to reduce turnover not just at line employees and supervisors but also at senior-level managers as well. Third, this study sheds light on the ongoing debate over "female advantage" in leadership (Eagly and Carli, 2003a, b; Vecchio, 2002, 2003) by examining not just how women are treated, but how their experience may reshape managerial dynamics.